PECULIARITIES OF DISTRIBUTION AND COMPOSITION OF BETAFITE FROM DIFFERENT FORMATIONS OF THE ALDAN SHIELD (SAKHA-YAKUTIA) - Guliy, V.; Poberezhska, І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Character of Nb and Ta distribution in the different geological formations of the Aldan Shield are given in this article. To get idea about betafite from different endogenic etalon formations the authors analyzed its well known locations in the pegmatites, skarns, carbonatites, metasomatites and late veins segregations. Geological setting and mineralogical composition of the apatite-bearing rocks from the Aldan Shield are described, and the most significant in scale metamorphosed carbonate and silicate varieties among them have been distinguished. Apatite mineralization in magnesium skarns and metasomatites is developed locally. Titanite and betafite are the main concentrators of Nb and Ta and apatite is typical accompanying mineral in the studied rocks. Betafite was detected in the pegmatite bodies from magnesium skarns and metasomatites of the Shield with irregular distribution within rocks rich and poor in apatite, but was not found in the most developed apatite-carbonate rocks which are regarded as ores of the Seligdar type, so it cannot be mineralogical indicator for this type of ores. Late carbonate generations are significantly enriched in light carbon and oxygen isotopes in contrast to positive δ13С values in apatitecarbonate bodies of the Seligdar deposit and its family and the highest δ18О values. We used these indicators to distinguish origin of the rocks with various carbonate generations, which have different amounts of betafite. Appearance of betafite is determined by primary composition of the initial rocks. Chemical composition of betafites from the skarns and metasomatites is similar, but with local variations. The most significant feature of the mineral composition is very low Ta content. Titanite is characterized by variable amounts of Nb and Ta in scale of sectors as well as within separate grains.
Keywords: betafite; titanite; Nb and Ta; metamorphic apatite-carbonate ores; Aldan Shield; pegmatites; metasomatites; skarns; carbonatites; C–O isotopes